(untitled) (Journal of the College of Basic Education, 2022)
The current research goal is to:1- Designing a model teaching plan to develop the technical capabilities of primary school students in implementing educational aids (designing three-dimensional shapes) according to the learning facilitation model.2- Measuring the effectiveness of the teaching plan by applying it to a sample of primary school students.In order to achieve the validity of the second objective, the researcher set a zero hypothesis and one that defines the current research with the fifth grade primary students of Al-Mahj School affiliated to the First Rusafa Education Directorate for the academic year 2011-2012, as well as the learning facilitation model set by (Carl Rogers). The current research took the experimental approach with partial control with one sample and two tests (pre and post) for the skill side.